How work and workers influence politics – Analysing the nexus through power resource theory - Refslund, Bjarke; Arnholtz, Jens (Journal of Political Sociology, 2025)
The conjunctures between work, economy and the political system continues to be a core issue within sociology. In this article we discuss how power resource theory can provide an analytical and theoretical lens that can enrichen our understanding of the nexus between work, labour markets and politics, through the concept of labour politics. Here we emphasise how power and the power resources of labour (still) matters so that workers and unions with more power resources can secure better conditions in the labour market, and we discuss the most important mechanisms through which the realm of work and broader societal outcome are linked